The use of artificial intelligence in counter-disinformation: a world wide (web) mapping - Pilati, Federico; Venturini, Tommaso (Frontiers in Political Science, 2025)
Disinformation has recently become a subject of widespread concerns across the globe. To combat this issue, various initiatives have emerged, aimed at identifying, tracking, and debunking disinformation. Artificial intelligence (AI) has been incorporated as a tool to counter disinformation, but its implementation has not always been successful and may even be counterproductive. Thus, there is a growing recognition of the need for benchmarking the various ongoing efforts to ensure greater efficacy and coordination in the use of AI and assure that this does not lead to forms of algorithmic censorship. Our goal is to provide a mapping of the projects that use AI to counter disinformation by means of their hyperlink network analysis to shed light on their aims, approaches, and challenges.